BAHASA SEKSIS DALAM KAMUS BESAR BAHASA INDONESIA - Ening Herniti (Sunan Kalijaga State Islamic University Yogyakarta, 2013)
Sexist language is the language which represents men and women are not equal that one member of the group considered inferior human sex, simpler, less rights than members of the other sex. Sexist language is usually present harmful stereotypes of women. From the Indonesian vocabulary contained in KKBI found vocabulary related to gender disparities. Vocabulary is gender biased unbalanced or asymmetrical. Data captured by the technical documentation of KBBI fourth edition in 2012. With descriptive methods, data will be analyzed critically. Indonesian system actually gives equal space to both men and women. However, the development of Indonesian in a few loanwords vocabulary especially gender discrimination. Asymmetric use of language not only treats women unfairly, but also can simplify the unfair treatment of women.